Emergency remote teaching and the adoption of digital technologies in higher education: The tase of a Portuguese tourism faculty - Pires, Ana (2022)
The global spread of COVID-19 affected all areas, including education, with teaching and learning having to take place online and on digital platforms. With very little to no time to prepare for this change, most higher education institutions resorted to emergency remote teaching (ERT) as the response to maintain instructional continuity in the face of the global health crisis. This sudden transition to online education brought new challenges for higher education lecturers, who were forced to adjust from face-to-face to online learning and to explore a plethora of digital tools to keep teaching and assessing remotely. By means of a survey conducted among the tourism faculty of a higher education institution in Portugal, the purpose of this study is to identify which digital tools and resources were adopted during the transition from traditional classroom teaching to ERT, and explore the main difficulties experienced by faculty in this challenging period.